Multiple mode exciton-vibrational coupling in H-aggregates: synergistic enhancement of the quantum yield - Spano, F C; Silvestri, Leonardo (The Journal of chemical physics, 2010)
The impact of exciton-vibrational coupling involving fast and slow vibrational modes on absorption and emission in molecular H-aggregates is investigated using a multimode Holstein Hamiltonian. For H-aggregates composed of rigid molecules the radiative decay rate is rigorously zero due to the asymmetry of the lowest energy exciton. Increasing the Huang-Rhys factors of the coupled modes results in an increase of the radiative efficiency through increased sideband emission. Coupling to a spectrally unresolved slow mode leads to an apparent increase in the 0-0 intensity of the vibronic progression of the fast mode, thereby mimicking a distribution of molecular transition frequencies (diagonal disorder). In the intermediate coupling regime, the radiative efficiency of the aggregate exceeds the sum of the fast-mode-only and slow-mode-only radiative efficiencies. The mechanism underlying the synergistic enhancement of the radiative yield is similar to that which causes spectral splitting in the absorption spectrum of quaterthiophene crystals. [L. Silvestri et al., J. Chem. Phys. 130, 234701 (2009)]. The results here qualitatively account for the robust emission efficiency of hexaphenyl microcrystallites where the slow torsional motion involving the interphenyl dihedral angle in conjunction with the fast ring breathing mode conspire to enhance the quantum yield.